2006
DOI: 10.1016/j.jpcs.2006.01.084
|View full text |Cite
|
Sign up to set email alerts
|

Tribological properties of low-temperature graphite fluorides. Influence of the structure on the lubricating performances

Abstract: International audienceThe present work is concerned with the study of the tribological properties of various fluorinated carbon phases obtained at room temperature and then post-treated under fluorine atmosphere at different temperatures. The tribological tests evidence good intrinsic properties for all the compounds (friction coefficient in the range 0.07-0.09). Differences appear after few cycles. Friction measurements after 100 cycles and complementary Raman analyses of the tribofilm remaining in the wear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 12 publications
4
27
0
1
Order By: Relevance
“…5), the D peak at 1348 cm -1 and a composite one centred at 1612 cm -1 , this last peak resulting due to the G and D' overlap. As previously mentioned in the literature [10], the I D /I G intensity ratio increases as a function of disorder in the carbon material. The I D /I G ratios in the initial CNFs and in the tribofilm are, respectively, 0.4 and 1.7 pointing out a drastic increase of disorder corresponding to the transformation of part of the initial CNFs into ill-organized carbon material in the final tribofilm during the friction process.…”
Section: Study Of the Tribofilmsupporting
confidence: 70%
See 1 more Smart Citation
“…5), the D peak at 1348 cm -1 and a composite one centred at 1612 cm -1 , this last peak resulting due to the G and D' overlap. As previously mentioned in the literature [10], the I D /I G intensity ratio increases as a function of disorder in the carbon material. The I D /I G ratios in the initial CNFs and in the tribofilm are, respectively, 0.4 and 1.7 pointing out a drastic increase of disorder corresponding to the transformation of part of the initial CNFs into ill-organized carbon material in the final tribofilm during the friction process.…”
Section: Study Of the Tribofilmsupporting
confidence: 70%
“…These compounds present good lubrication properties as the obtained friction coefficients are similar to those of conventional graphite fluorides. We showed that several parameters such as the nature of the C-F bonds, the presence and the nature of intercalated species and the fluorine content strongly influence the tribological properties of the fluorinated phases [10].…”
Section: Introductionmentioning
confidence: 98%
“…The coexistence of sp 2 and sp 3 carbon atoms confers to these materials interesting electrochemical properties for primary lithium batteries [16]. We showed in a previous work that the compounds obtained in the case of F 2 , HF, and IF 5 mixture present rather good tribologic properties, influenced by the nature of the C-F bonds, the presence of intercalated species and the fluorine content [17].…”
Section: Introductionmentioning
confidence: 91%
“…Recently synthesized CF [16] is similar to CH, but F atoms are negatively charged. Tribological properties of carbon based fluorinated structures have been the focus of interest [23,24]. In the layers of MoS 2 or WO 2 , the plane of positively charged transition metal atoms is sandwiched between two negatively charged outer S or O atomic planes.…”
Section: Superlubricity Between Two Layers Of Graphene Derivatives Anmentioning
confidence: 99%